DEVELOPING INTERACTIVE EDUCATIONAL COMICS ON LOCAL CULTURE TO ENHANCE CRITICAL THINKING SKILLS - Try Supryanto; Hardyanti Hardyanti; Sri Suryaningsih; Anita Putri; Arwan Arwan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Critical thinking skills are essential 21st-century competencies that should be developed from elementary education. However, students often struggle with higher-order thinking, worsened by the lack of engaging and contextual learning media. This study addresses the issue by developing interactive educational comics based on local culture through a fun learning approach to enhance students’ critical thinking. The study aims to produce learning media that are valid, practical, and effective in supporting arts and culture education while improving critical thinking skills. Using a Research and Development (R&D) approach with the ADDIE model (analysis, design, development, implementation, evaluation), the research involved 71 fourth-grade students from SDN Bajo and SDN Wadukopa. Instruments included validation sheets, critical thinking tests, and questionnaires for teachers and students. The final analysis used a t-test and n-gain test. Results indicate the comics are valid based on expert evaluation, highly practical according to teacher and student responses, and effective in improving critical thinking. The t-test (sig. 0.000<0.05) confirmed significant differences in students’ skills before and after implementation, while the n-gain test showed a 96% increase. Thus, the interactive educational comic proves to be a feasible and impactful medium for developing critical thinking in elementary students.